PSYCHOPHYSOCIAL ASPECTS DURING AND AFTER VAS SUPPORT - YAMAGUCHI, Y.; MIZUKAMI, C.; UEZINO, E. (Jinko Zoki, 1998)
In patients having a progressively deteriorated general condition and wating for cardiac transplantation, ventoricular assisting device (VAS) is undoubtedly effective so as to improvetheir physical circumstances. Their quality of life, however, is not necessarily ideal. At our institution, 5 patients have undergone circulatoly support using VAS. In one of these, coming off VAS could be successfully achieved because of fortunate recoveryof ventoricular function.Quality of life was evaluated in this paticular patient in terms of physical and phychosocialaspects digitised by Sickness ImpactProfile (SIP), as well as degree of depression by Self rating Depression Scale(SDS) which can be an indicator of mental health. Physically, an impact score was increased by initiation of VAS, and extention of ADL decreased the impact. It was decreased still further with stable course after coming off VAS. As for phychosocial aspect, although change in score was similar to that seenin the physical aspect until ADL was considerably extended, it proved that prolonged use of VAS was a deleterious factor, increasing again the impact in this patient. SDS demonstrated no influence of initiation and termination of VAS on mental depression in this case